A graveyard smash: analyzing embodied memories in Lincoln in the Bardo - Vorbeck, Cara (Style, 2023)
ABSTRACT. This article explores the concept of embodied memory in literary fiction and aims to illustrate some of the many angles from which it can be examined. After reviewing three different approaches to understanding embodied personal memory, it argues in line with contemporary perspectives on embodiment and 4E cognition (Caracciolo and Kukkonen) that a combined approach of cognitive and more traditional perspectives on the concept has significant benefits for analyzing embodied memories in literary texts. A case study of Lincoln in the Bardo (2017) is presented to illustrate these claims in practice. The analysis shows that a medial or symbolic approach to embodied memory cannot contain the novel’s complex bodies on its own and that a cognitive perspective adds an analytic layer which is essential to forming an understanding of its personal as well as collective mechanics of remembrance.
Online veröffentlicht: 17. August 2023
Gesehen am 25.10.2023